The Directions of Tourists’ Destinations in Rwandz and Soran Districts in Kurdistan, Iraq between 2013-2018 - Hamadamin, Amanj (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Human movements and their travel in the world has gone through various stages throughout history. Tourism plays a significant role in the economic sector and increases national revenue. Therefore, it impacts the growth and development of areas that have attractive natural and physical features. Studying the variations in tourists’ destinations can be helpful to understand tourists’ behavior and its influence on the development of touristic sites according to their characteristics and tourists’ demands in the future. The main aim of this research is to study tourists’ movements in Soran and Rwandz district sites between 2013-2018 using the Geographic Information System (GIS) and R program. In this study, data on the movement of tourists in Rwandz and Soran districts are obtained from the General Board of Tourism in the Kurdistan Region of Iraq and the Soran Tourism Directorate. The tourist sites in the study are Ali Beg Valley, Pank Tourist Resort, Bekhal Summer Resort, Korek Mountain Resort and Jundian Summer Resort. Graphs and statistical calculations of trend were processed in R, a programming language and open-source environment for statistical computing and graphics. This research shows that in 2013, 83076 tourists visited Soran and Rwandz district tourist sites, but after 2018, compared to the previous years, the figures showed an increase of visitors to 97073 tourists. From 2013 to 2018, Arab tourists contributed the most, and their numbers increased from 26136 to 42838. The number of tourists towards Pank Resort peaked with 70586 tourists, but in 2018, there was a change in the destination of tourists towards Ali Galley Bag waterfall with 25116 visitors.